2013
DOI: 10.3390/ijerph10010314
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Diagnostic Radiation Workers in Korea from 1996–2002

Abstract: This study was aimed to examine the association between the effective radiation dose of diagnostic radiation workers in Korea and their risk for cancer. A total of 36,394 diagnostic radiation workers (159,189 person-years) were included in this study; the effective dose and cancer incidence were analyzed between the period 1996 and 2002. Median (range) follow-up time was 5.5 (0.04–7) years in males and 3.75 (0.04–7) years in females. Cancer risk related to the average annual effective dose and exposure to more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Previous cohort studies of medical radiation workers revealed increased risk of solid cancers of the breast, stomach, thyroid, brain, colon, and nonsolid cancers such as leukemia and lymphoma as well as cardiovascular diseases and radiogenic cataracts. Although the excess risks were evident in the earlier period of radiologic practice, the potential hazards of current low doses and low‐dose‐rate radiation to the radiation workers cannot be ruled out because of the stochastic effects of ionizing radiation that the probability of health effects is regarded as a linear nonthreshold function of the dose.…”
mentioning
confidence: 99%
“…Previous cohort studies of medical radiation workers revealed increased risk of solid cancers of the breast, stomach, thyroid, brain, colon, and nonsolid cancers such as leukemia and lymphoma as well as cardiovascular diseases and radiogenic cataracts. Although the excess risks were evident in the earlier period of radiologic practice, the potential hazards of current low doses and low‐dose‐rate radiation to the radiation workers cannot be ruled out because of the stochastic effects of ionizing radiation that the probability of health effects is regarded as a linear nonthreshold function of the dose.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The use of radiation in the diagnosis and management of stone disease is common and has distinct advantages to other imaging modalities. Exposure to ionizing radiation should be minimized whenever possible.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of radiation exposure and risk associated with gastrointestinal malignancy comes from CT scans, especially of the abdomen and pelvis; the colon carries the highest lifetime attributable risk of radiation associated malignancy (Chang and Hou, 2011). Besides patients, cancer risk of colon and rectum cancers in male diagnostic radiation workers in Korea also showed a significantly increasing trend according to the increase of the average annual radiation dose (HR: 2.37) (Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 98%